A Comparative Study of the Antimicrobial Effect of Scrophularia striata Boiss. Extract and Selective Antibiotics Against Staphylococcus aureus and Pesudomonas aeroginosa - N Abbasi; F Azizi Jalilian; M Abdi; M Saifmanesh (Institue of Medicinal Plants, ACECR, 2007)
Background: The pathogen of the positive gram Staphylococcus aureus and the negative gram Pseudomonas aeroginosa are the most important infectious factors for human. Since the bacterial resistance to the chemical medicines has increased and the plant medicines are of less side effects, nowadays the medical plants have been the focus of attention.   Objective: In this research, the Staphyloccus aureus and pseudomonas aeroginosa have been isolated. The pathogen of staphylococcus positive gram bacterium and pseudomonas aeroginosa negative gram after being isolated, they were incubated in a special condition .   Results: An extract obtained from a native plant called Scropholaria striata. Then some incubation conditions were prepared * from 15 to 4 mac suspensions of these bacteria. To determine the sensitivity, two micro well were made in each incubation condition. In one of the micro well the plant extract and in the other one the positive control 2 i.e. Amikacin and vancomycin were poured, of course with the different densities. After measuring the circle made out of it, the results were studied.   They showed that the average of the circle diameters made by scropholoria striate was more than that made by chemical medicines with positive control (p<0.05). Increasing the density of the extract from 50 microlitre to 90 microlitre, the average of the circle diameters increased (p<0.05).   The achieved results showed that more number of the bactera in each incubation condition, the less the diameter of staphylococcus aureus circle (p<0.05), but for a genus of pseudomonas the result was not the same. Conclusion: The final results of the research showed that the plant extract of Scropholaria striata can be used as an alternative remedy of the infections coused by these two microorganisms.